2021
DOI: 10.1111/jop.13159
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of oral and maxillofacial acinic cell carcinoma: A systematic review

Abstract: Background The aim of the present systematic review was to analyze the available data regarding acinic cell carcinoma of the oral and maxillofacial region. Methods A search strategy was performed using PubMed, Web of Science, Scopus, and Embase electronic databases. Results Available data revealed a slight female preference (54.73%) and a mean age at diagnosis of 47.51 ± 19.85 years. The parotid glands (67.72%) were most frequently affected, and most cases were asymptomatic (69.54%). A microcystic histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…AciCC with high-grade transformation is considered to be more aggressive and predictive of recurrence and distant metastases; despite a histologic grading system is still lacking, frequent mitosis, ki-67 proliferation > 5%, perineural and vascular invasion, infiltration and tumour necrosis are regarded as high-grade features, explaining the aggressive behaviour of these dedifferentiated tumours [ 21 , 22 ]. The largest case series reported by Scherl et al [ 9 ] found a subgroup of patients with high-grade features showing poor outcomes, suggesting how histologic grade can be a stronger predictor of surgical than T and N classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AciCC with high-grade transformation is considered to be more aggressive and predictive of recurrence and distant metastases; despite a histologic grading system is still lacking, frequent mitosis, ki-67 proliferation > 5%, perineural and vascular invasion, infiltration and tumour necrosis are regarded as high-grade features, explaining the aggressive behaviour of these dedifferentiated tumours [ 21 , 22 ]. The largest case series reported by Scherl et al [ 9 ] found a subgroup of patients with high-grade features showing poor outcomes, suggesting how histologic grade can be a stronger predictor of surgical than T and N classification.…”
Section: Discussionmentioning
confidence: 99%
“…Acinic cell carcinoma (AciCC) is the fourth most common epithelial tumour of salivary glands after mucoepidermoid carcinoma, adenocarcinoma (not otherwise specified, NOS) and adenoid cystic carcinoma [ 1 ]; it can be considered an extremely rare tumour (it comprises 9–11% of all adult parotid malignancies) [ 2 ] and its incidence has been previously described by the Surveillance of Rare Cancers in Europe Working Group (RARECARE) as 1.20–1.63 cases per 1,000,000 patients/years [ 3 ]. The definition of AciCC is constantly evolving over time; first observed in 1892 from Nasse [ 4 ] as a benign lesion and called “adenoma”, it was described by Buxton et al [ 5 ] as a malignant tumour with the ability to metastasize and recur.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases presented as an indolent mass. 5 Histologically, AciCC shows four main patterns: solid, papillary cystic, microcystic, and follicular. These patterns may occur individually or in combination, without a prognostic significance.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns may occur individually or in combination, without a prognostic significance. 5,6 Although AciCC Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…A cinic cell carcinoma (AciCC) is a low-grade carcinoma characterized by acinic cell differentiation, comprising ~10% of salivary gland carcinomas. [1][2][3][4] With the advent of genetic analysis, an increasing number of gene and chromosome aberrations have been identified, offering new potential avenues for investigating both differential diagnosis and prognosis of a spectrum of salivary gland carcinomas. 5 For instance, the CRTC1/3::MAML2 fusion 6 has been reported in mucoepidermoid carcinoma and tends to be associated with favorable survival rates.…”
mentioning
confidence: 99%